2006
DOI: 10.1007/s00134-006-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

Constant flow insufflation of oxygen as the sole mode of ventilation during out-of-hospital cardiac arrest

Abstract: CFIO is a simplified alternative to MV, with favorable effects regarding oxygenation and fewer complications, as observed in this group of patients with desperate prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 27 publications
2
45
0
6
Order By: Relevance
“…However, 3 additional studies (LOE 1 244 ; LOE 2 245 ; LOE 5 246 ) failed to consistently show improvement in survival to hospital discharge when compression-only CPR compared with conventional CPR was administered by professionals to adult patients with an OHCA.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…However, 3 additional studies (LOE 1 244 ; LOE 2 245 ; LOE 5 246 ) failed to consistently show improvement in survival to hospital discharge when compression-only CPR compared with conventional CPR was administered by professionals to adult patients with an OHCA.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…93,94 A third study compared bag-mask ventilation to high-flow oxygen delivery by nonrebreather face mask after oropharyngeal airway insertion as part of a resuscitation…”
Section: Evidence Summarymentioning
confidence: 99%
“…Two studies (LOE 1), 156,157 involving ALS providers in-and out-of-hospital settings, and 2 animal studies (LOE 5) 158,159 suggested that passive oxygen delivery through a Boussignac tube at a flow of 15 L/min associated with continuous chest compressions (with or without active compressiondecompression CPR) generated equal or improved gas exchange and hemodynamics, but without improved outcome (ROSC, hospital discharge survival, or neurological outcome), when compared with a standard tracheal tube and positive pressure ventilation.…”
Section: Consensus On Sciencementioning
confidence: 99%